Do controle de constitucionalidade dos atos jurisdicionais transitados em julgado - Marques, Andreo Aleksandro Nobre (2007)
The following study aims to verify in which hypothesis res judicata, when it comes of an unconstitutional decision, shall not prevail over Constitution. It displayed the characteristics of formal and material constitutional systems. It debated the concepts of existence, validity and efficacy of juridical rules and acts. It dissertated about the idea of Constitution s superiority and about the birth of the judicial review of constitutionality. It focused some contemporary models of this judicial review and its historical evolution in Brazil, showing its effects towards the current Constitution. It sustained that the decision given by Supremo Tribunal Federal during abstract control of rules must bind even legislative bodies, preventing them to produce the same rules previously declared unconstitutional. It held up that all parts of the decision of Supremo Tribunal Federal oblige, even the juridical arguments employed, in both diffused and concentrated reviews. It showed that, despite these models of review live together in Brazil, our constitutional system preferred the concentrated one, considering one only court over the other constitutional organs. It discussed about res judicata with the purpose of clarifying its juridical nature, its objective and subjective limits and its regulation in collective demands. It explained that the material res judicata is an effect of a decision which cannot be reviewed, which makes the law s will free of discussion, binding the contendants and avoiding that other courts, judging future demands about the same object, may decide differently. It showed how the regulation of res judicata in collective demands, in respect oh their subjective limits, is useful to demonstrate that it is not the material law who must adapt itself to res judicata as traditionally thought, but res judicata, as a warranty of juridical certainty and security, who must be shaped from the debated rule. It presented to view the main doctrinal conceptions about res judicata s review in the hypothesis of unconstitutional judgement. It concluded that the decisions forged by unconstitutional rules or interpretations reputed not compatible to the Constitution by Supremo Tribunal Federal, in spite of it can make res judicata, may be reviewed beyond the term to file a recissory claim, since while the debated law is still valid, no matter if its decision was before or after the res judicata. At the end, it asserted that, when it is not legally authorized, the judicial review of res judicata is not admissible, after the term to file a recissory claim, under the argument that there was no direct violation to the constitutional principle or rule